KUALITAS SISTEM, KUALITAS INFORMASI, KETEPATAN WAKTU, KERAHASIAAN DAN KEPUASAN WAJIB PAJAK PENGGUNA E-FILING - Dina Dwi Ningrum; Andi Andi (FEB Universitas Sultan Ageng Tirtayasa, 2016)
Quality of the system in this research is to look at the e-filing system that is easy to use, e-filing system is equipped with useful features and functions to make data changes with ease, and security of e-filing system was good. The quality of the information in this study is the information contained in the e-filing system is accurate, the presentation of information in the e-filing is clear, and the information presented in accordance with user needs. Timeliness in this study is seen by inputting the data with the e-filing system can be done quickly, and e-filing system whether it can make the user into saving time in sending data. Confidentiality in this study is based on whether the e-filing can only be accessed by authorized persons only (users only), user data can not be altered without the permission of the authorities, the data will be available when needed if the user is authorized to access, and users trust the system e-filing can maintain data confidentiality. How large is the Effect of Quality Systems, Information Quality, Punctuality and Confidentiality of Taxpayer Satisfaction User's E-Filing Keyword: QUALITY SYSTEMS, QUALITY INFORMATION, TIMELINESS, CONFIDENTIALITY, SATISFACTION OF TAXPAYERS USER E-FILING